Industrial Relations in Southern Textile Mills - Gulick, Charles A. (Quarterly Journal of Economics, 1932)
Journal Article Industrial Relations in Southern Textile Mills Get access Charles A. Gulick, Jr. Charles A. Gulick, Jr. University of California Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 46, Issue 4, August 1932, Pages 720–742, https://doi.org/10.2307/1882814 Published: 01 August 1932